Safety profiles of beneficial lactic acid bacteria isolated from dairy systems - Colombo, Monique (Braz J Microbiol, 2020)
This study aimed to assess the safety aspects of 15 lactic acid bacteria (LAB) strains previously isolated from a dairy environment with relation to their beneficial features. LAB strains were assessed using phenotypic methods according to their production of virulence factors at 25 °C and 37 °C, as well as by examining their potential resistance to 15 antibiotics. Polymerase chain reaction (PCR) was also used to identify the presence of 50 genes associated with virulence factors and antibiotic resistance in the strains. None of the strains presented hemolytic activity or the production of gelatinase, lipase, deoxyribonuclease, or the tested biogenic amines. Based on the disk diffusion assay, all strains were resistant to oxacillin and sulfa/trimethoprim. Further, some were resistant to gentamicin (14), clindamycin (11), vancomycin (9), rifampicin (8), erythromycin (5), tetracycline (4), ampicillin (2), and chloramphenicol (1); no strain was resistant to imipenem. Regarding virulence- and antibiotic-resistance-related genes, 19 out of 50 tested genes were present in some strains; there was a variable association of expression. Based on the obtained data, the isolates presented relatively safe characteristics and behavior, findings that should lead to further studies to assess their potential usage as beneficial cultures in the food industry.